2020
DOI: 10.3389/fmed.2020.542567
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Assessment of Endothelial Function in Humans

Abstract: The endothelium is recognized to play an important role in various physiological functions including vascular tone, permeability, anticoagulation, and angiogenesis. Endothelial dysfunction is increasingly recognized to contribute to pathophysiology of many disease states, and depending on the disease stimuli, mechanisms underlying the endothelial dysfunction may be markedly different. As such, numerous techniques to measure different aspects of endothelial dysfunction have been developed and refined as availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 237 publications
(208 reference statements)
0
47
0
7
Order By: Relevance
“…However, it should be mentioned that no direct correlation between endothelial dysfunction biomarkers and changes in endothelial function assessed by FMD has been documented to date. Moreover, vascular biomarkers might not directly reflect the local tissue environment [ 55 , 56 , 57 ]. Schjerve et al [ 26 ] observed that both endurance and strength training significantly improve endothelial function measured as FMD in obese subjects after 12 weeks of intervention, but high-intensity aerobic training was more effective in the improvement of endothelial function compared with strength training and moderate-intensity groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be mentioned that no direct correlation between endothelial dysfunction biomarkers and changes in endothelial function assessed by FMD has been documented to date. Moreover, vascular biomarkers might not directly reflect the local tissue environment [ 55 , 56 , 57 ]. Schjerve et al [ 26 ] observed that both endurance and strength training significantly improve endothelial function measured as FMD in obese subjects after 12 weeks of intervention, but high-intensity aerobic training was more effective in the improvement of endothelial function compared with strength training and moderate-intensity groups.…”
Section: Discussionmentioning
confidence: 99%
“…Microvasculature assessment will be done via retinal imaging using a retinal camera (Optomed, Finland) as previously reported [ 40 ]. Blood samples will be collected for the assessment of endothelial function markers [ 41 ], oxidative stress, lipid profile and insulin resistance markers [ 42 ] while urine will be collected for assessment of renal function. Mothers will have one post delivery follow-up for CVD risk assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Към настоящия момент са описани множество неинвазивни и минимално инвазивни методики за оценка на микроциркулацията, които през годините са имали различен принос в диагностичния процес [25,26,27]. С развитието на технологиите на преден план се оказаха методики като лазер-доплер флоуметрията (и нейните модернизирани вариации), както и капиляроскопията и видеокапиляроскопията.…”
Section: фиг 8 видеокапиляроскопияunclassified
“…Up to this date, many non-invasive and minimally invasive methods for assessing microcirculation have been described, which over the years have had different contributions to the diagnostic process [25,26,27]. With the development of technology, techniques such as laser Doppler flowmetry (and its modernized variations), as well as capillaroscopy and videocapillaroscopy have come to the fore, they have found a place both in everyday practice and in numerous clinical trials.…”
Section: Fig 8 Video Capillaroscopymentioning
confidence: 99%